Kreativitas Partonun dalam Menimbulkan Efek Komunikasi Pemasaran Ulos - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2009)
AbstractThis article about ulos, a traditional clothes made by Batak People. Nowdays, many partonun (people who made ulos) difficult to sell it. They complain about that and finally did not serious to preserve this culture. As a traditional ancestor heritage ulos must be competing in this global market era.So actually they need a new creativity to think how ulos can be more impotant. This Writing want to think about creativity by using communicatioan market theories.